Soil radon monitoring and anomalies in East Anatolian Fault System (Turkey) - Baykara, O.; Inceoez, M.; Dogru, M.; Aksoy, E.; Kuelachi, F. (Springer, 2009)
On-line monitoring of soil radon (Rn-222) concentration system was constructed on one of the main active fault zone of East Anatolian Fault System (EAFS) in Turkey. The preliminary results, observed during the second part of 2004 and first part of 2005 is presented. During the monitoring of soil radon concentration, numerous anomalies that equal or twice standard deviation were observed. In addition, the variation of the radon concentration was examined between the mean values and plus/minus two standard deviations and any increase in radon concentration above this limit was assumed to be Rn-222 anomalies. These anomalies usually appeared between a few days or weeks before the earthquakes occurrence. The obtained data were also compared as considered respect to the earthquakes occurred in a 100 km radius of the fault system.
Keywords: Uranium Concentration; Gas Geochemistry; Earthquake; Samples; Prediction; Emanation; Rn-222; North